Winter Diets of Brown Trout Populations in Southeastern Minnesota and the Significance of Winter‐Emerging Invertebrates. Issue 1 (8th January 2016) - Anderson, A. M.; Mittag, E.; Middleton, B.; Vondracek, B.; Ferrington, L. C.
Abstract: Winter is a critical period for stream‐dwelling trout, and the need to extend investigations into this period has long been recognized. The intent of this research was to investigate the winter diet of Brown Trout Salmo trutta, as only a limited number of studies have focused on winter dynamics and how the winter macroinvertebrate community affects trout during winter. Our specific objectives were to assess variability in winter diet of different size‐classes of trout, determine whether fish exhibit size‐selective predation, quantify the extent that trout differentially exhibit drift or benthic feeding, and assess the importance of winter‐emerging insects in the winter diet. Stomach contents from 30 Brown Trout were collected from three streams on six occasions during the winter of 2010 and compared with macroinvertebrates collected in the drift and from the benthos. Trout in each stream exhibited distinct diets, and diets of larger fish differed from those of smaller fish; larger trout consumed greater amounts of Trichoptera and Physella and smaller fish ingested more Gammarus and Chironomidae larvae. Stomach contents of both sizes of fish were more similar to the benthos than drift, indicating fish had a greater reliance on benthic feeding in winter. When considered across all streams, trout preferentially selected Trichoptera and Chironomidae and maintained size‐selective predation throughout the winter, selecting larger Gammarus and Chironomidae larvae than typically found in the environment. However, winter‐emerging Chironomidae appeared to enhance diets in all three streams, and chironomid larvae were particularly dominant in the diet of one trout population. Variations in abundance of winter‐emerging insects between streams may impact the winter condition of Brown Trout, particularly in smaller fish, which were found to feed more heavily on these organisms. These findings may have important implications for fisheries management.